PENGGUNAAN MEDIA GAMBAR UNTUK MENINGKATKAN MINAT BELAJAR PKn SISWA KELAS II SDN 015 PAGARAN TAPAH DARUSSALAM - Asmaria Asmaria (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2017)
This research is motivated by the low interest students learning civics class II SDN 015 Pagaran Tapah Darussalam. Goals to be achieved in this research is to improve the interest in learning civics grade II SDN 015 Pagaran Tapah Darussalam through the use media pictures conducted during one month. This research was conducted in SDN 015 Pagaran Tapah Darussalam. Classes are meticulous researcher is a class II half of the number of students as many as 20 people. This classroom action research was started in early august 2015. This form of research is classroom action research. The research instrument consists of instruments teacher and student activity sheets and achievement test. Based on the analysis and discussion can be concluded that the success of the study is known of improving learning at each meeting for each cycle. The first cycle of the first meeting of student interests is still considered low by percentage of 48.3%. The first meeting of the second cycle increased with the percentage of 58,3%, in the first meeting of the second cycle also increases with the percentage of 70,8%, student interest in the percentage reached 80,00% or higher category. Thus the research hypothesis that says the use of media images can increase increase student interest in learning civics class II SDN 015 Pagaran Tapah Darussalam